2020
DOI: 10.1097/j.pain.0000000000002045
|View full text |Cite
|
Sign up to set email alerts
|

Novel bifunctional hybrid compounds designed to enhance the effects of opioids and antagonize the pronociceptive effects of nonopioid peptides as potent analgesics in a rat model of neuropathic pain

Abstract: Supplemental Digital Content is Available in the Text. The role of nonopioid peptides derived from opioid prohormones in neuropathic pain hypersensitivity and an indication of the hybrids as candidates for drugs in neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…The results of neuropathic pain on MC4R levels in other regions of the CNS are more consistent, with groups showing increases in MC4R in spinal regions, including the dorsal horn of the spinal cord, specifically in localized to layers I and II(65,69,94,95), and supraspinal regions that mediate pain transmission including the PAG(72). Interestingly, MC4R antagonism not only reverses neuropathic-like pain states in preclinical models(48,65,69,74,75,94…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…The results of neuropathic pain on MC4R levels in other regions of the CNS are more consistent, with groups showing increases in MC4R in spinal regions, including the dorsal horn of the spinal cord, specifically in localized to layers I and II(65,69,94,95), and supraspinal regions that mediate pain transmission including the PAG(72). Interestingly, MC4R antagonism not only reverses neuropathic-like pain states in preclinical models(48,65,69,74,75,94…”
mentioning
confidence: 62%
“…Recently, compounds that have a pharmacophore containing an enkephalin analog (Tyr-D-Ala-Gly-Phe) and MC4R antagonist derived from SHU9119 (Nle-c[Asp-His-2'- D Nal-Arg-Trp-Lys]) connected by various linkers have been developed. Results from these studies have indicated that these compounds have much lower effective doses as indicated by 50% effective dosages that were on the order of 1,000–10,000 times lower than parent compounds, for producing analgesia under preclinical models of nerve injury (i.e., chronic constrictive injury to the sciatic nerve) ( 74 , 75 ). For instance, one of the hybrids (UW3) induced analgesia 1,500 times greater relative to the parent opioid receptor compound alone and 16,000 times greater to the parent melanocortin receptor compound alone, respectively in male CD-1 mice subjected to nerve injury ( 74 , 75 ).…”
Section: Melanocortin System and Painmentioning
confidence: 99%
“…A large group of intensively studied compounds are also different hybrid compounds with mixed agonistic/antagonistic activity at either opioid or nonopioid receptors. Searching for compounds with complex receptor binding profiles allow synergy of therapeutic action and avoidance of some undesirable effects, e.g., agonism of μ-OR and δ-OR antagonism lead to antinociception with no tolerance [ 12 ], while bifunctional hybrids composed of opioid receptor agonist and MC4 receptor antagonist delay the development of tolerance in rats with neuropathic pain [ 124 ]. It is also worth mentioning that µ-δ-OR heterodimers may allow inducing antinociception with lower tolerance under repeated dosing [ 125 , 126 ].…”
Section: Low Intrinsic Efficacy and Partial Agonism Of Novel Compounds As Possible Causes Of Their Behavioral Profilesmentioning
confidence: 99%
“…The preclinical tests in rodent models of NP performed by our group allowed to select the compounds characterized by the best analgesic profile under nerve injury conditions. Further authorial modifications to the compounds’ structures, based on the preclinical evidence obtained, gave rise to the series of bifunctional ligands uniquely designed to treat neuropathic pain [ 94 , 95 ]. The basic studies on mice and rats subjected to sciatic nerve injury (CCI model) revealed that the linker type prominently influences the compound’s properties in vivo, determining the intensity and duration of the final analgesic effect.…”
Section: Neuropathy-involved Systems As Targets Of Hybrid Drugsmentioning
confidence: 99%
“…doses about hundred times lower than individual pharmacophores. The effect provided by single-target parent compounds, as well as their physical mix, was less pronounced and relatively short-lasting ( Scheme 3 ) [ 94 , 95 ]. The unique property of the OP-MC4 receptor hybrid, as compared to other ideas of bivalent compounds proposed for neuropathic pain treatment, is that its analgesic functions result from the modulation of a single nociception-related system, as the hybrid simultaneously enhances and suppresses the effects of different products derived from the same prohormone.…”
Section: Neuropathy-involved Systems As Targets Of Hybrid Drugsmentioning
confidence: 99%